Vascular Access Perspectives in Patients After Kidney Transplantation - Letachowicz, Krzysztof; Banasik, Mirosław; Królicka, Anna; Mazanowska, Oktawia; Gołębiowski, Tomasz; Augustyniak-Bartosik, Hanna; Zmonarski, Sławomir; Kamińska, Dorota; Kuriata-Kordek, Magdalena; Krajewska, Magdalena (Frontiers in Surgery, 2021)
Introduction: More attention has been paid to the influence of arteriovenous fistula (AVF) on the cardiovascular system. In renal transplant recipients, some beneficial effect of an elective vascular access (VA) ligation was observed in patients with a high AVF flow. However, this strategy is not widely accepted and is in contradiction to the rule of vasculature preservation for possible future access. The aim of our study is to elucidate the vascular access function and VA perspective in the kidney transplantation (KTx) population. Materials and Methods: KTx patients with a stable graft function were recruited to participate in this single center observational study (NCT04478968). The measurement of VA flow and vessel mapping for future vascular access was performed by a color Doppler ultrasound. The study group included 99 (63%) males and 58 (37%) females; the median age was 57 (IQR 48–64) years. The median time from the transplantation to the baseline visit was 94 (IQR 61–149) months. Median serum creatinine concentration was 1.36 (IQR 1.13–1.67) mg/dl. Results: Functioning VA was found in 83 out of 157 (52.9%) patients. The sites were as follows: snuffbox in six (7.2%), wrist in 41 (49.4%), distal forearm in 18 (21.7%), middle or proximal forearm in eight (9.6%), upper-arm AV graft in one (1.2%), and upper-arm AVFs in nine (10.8%) patients, respectively. Blood flow ranged from 248 to 7,830 ml/min; the median was 1,134 ml/min. From the transplantation to the study visit, 66 (44.6%) patients experienced access loss. Spontaneous thrombosis was the most common, and it occurred in 60 (90.9%) patients. The surgical closure of VA was performed only in six (4%) patients of the study group with a functioning VA at the time of transplantation. Access loss occurred within the 1st year after KTx in 33 (50%) patients. Majority (50 out of 83, 60.2%) of the patients with an active VA had options to create a snuffbox or wrist AVF on the contralateral extremity. In a group of 74 patients without a functioning VA, the creation of a snuffbox or wrist AVF on the non-dominant and dominant extremity was possible in seven (9.2%) and 40 (52.6%) patients, respectively. In 10 (13.1%) patients, the possibilities were limited only to the upper-arm or proximal forearm VA on both sides. Access ligation was considered by 15 out of 83 (18.1%) patients with a patent VA. Conclusions: In the majority of the patients, vascular access blood flow was below the threshold of the negative cardiovascular effect of vascular access. Creation of a distal AVF is a protective measure to avoid a high flow and preserve the vessels for future access. The approach to VA should be individualized and adjusted to the patient's profile.